PENGABDIAN KEPADA MASYARAKAT: JURI KARYA ILMIAH BERTEMA PEMANASAN GLOBAL - Rembulan, Glisina Dwinoor; Zubaedah, Siti Yasmina; Shen, Elza Jiuni; Nicholas, Nicholas (Jurnal Pengabdian dan Kewirausahaan, 2024)
Global warming is one of the most pressing environmental issues of the 21st century, with far-reaching impacts ranging from extreme climate change to threats to biodiversity and human life. The increase in the average temperature of the atmosphere and oceans, driven by human activities, particularly greenhouse gas emissions such as carbon dioxide, methane, and nitrous oxide, exacerbates this situation. Negative effects such as polar ice melting, rising sea levels, and ecosystem disruptions threaten the survival of many species. Growing global awareness of the importance of understanding and addressing global warming has led to various initiatives, including scientific competitions focused on global warming. These activities aim to educate the public and promote innovation in finding sustainable solutions to this environmental problem. In these competitions, the role of judges is crucial in evaluating the quality and relevance of the scientific works submitted by participants. Through community engagement carried out by the Management Study Program of Universitas Bunda Mulia in collaboration with SMA Kristen Tunas Bangsa Sunter Jakarta Utara, this competition successfully inspired and nurtured young generations in facing the challenges of global warming. The event included presentations, discussions, and Q&A sessions aimed at developing creative ideas and making a real contribution to global efforts in combating global warming.